TRADE NAMES IN THE TRADEMARK REGIME: COMEBACK OF THE FORGOTTEN TWIN? - Paul-George BUTA (Challenges of the Knowledge Society)
Just like Venus, once considered Earth’s twin and largely forgotten for more than 50 years, was back in the spotlight after an unexpected discovery, trade names, left in the shadows by their more successful ‘twin’ – trademarks, are surprisingly mentioned in the latest EU trademark Directive. Could this be the premise for a comeback of the forgotten right? We briefly analyze the position of trade names in the trademark regime before the new trademark Directive and the changes brought by the new EU act. Looking at the case-law and literature related to the previous regime, we argue that the premise the new regime was based on (in what concerns the interference between trade names and trademarks) is not accurate and that, as a consequence, an imbalance in the relative protection of these rights has been created. We propose that the appropriate remedy is the adopting, at the national level of the EU Member States, of specific legislation concerning the protection of trade names. Fortuitously, this would also allow some EU Member States to discharge an international obligation neglected for over a century.